Perceptions of Secondary School Science Teachers Regarding English-Medium Instruction: A Case Study - Kamran Akhtar Siddiqui (JSE, 2023)
Although English is used as a medium of instruction to teach science subjects in secondary schools in Pakistan, the perceptions of secondary school science teachers have remained underexplored. Therefore, this study aimed to explore the perceptions of secondary school science teachers regarding English as a medium of instruction in Pakistan. Using a qualitative case study approach, in-depth semi-structured interviews were conducted with four secondary school science teachers who were selected purposefully.